Legal regulation of disability cases - Saeed Reda, Assistant Lecturer Hassan (The college of law and political science journal, 2023)
A person may be born with one or more disabilities, in which case they should receive special treatment commensurate with their disability. Therefore, legislators in countries took notice and enacted laws to regulate the treatment of people with disabilities. On the international side, efforts resulted in the signing of a Convention on the Rights of Persons with Disabilities in 2006, to which most countries have acceded. The legislation dealt with the definition of disability, how to diagnose it, the body responsible for diagnosis, and the rights acquired by people with disabilities due to their disability. However, we will limit ourselves to the definition of disability, the statement of the person responsible for diagnosing it, the procedures required for that diagnosis, and finally the standard used to grant people with disabilities their rights. Where we will address the definition of disability in language and terminology, and we will find that there are two criteria for disability: the first is medical that focuses on the defect that affects a particular organ, and the second is comprehensive that adds social and environmental factors to the medical factor; and we will see the position of the International Convention on the Rights of Persons with Disabilities, which adopted the comprehensive criterion, and was followed by the Iraqi legislator in the Law on the Care of People with Disabilities and Special Needs No. (38) of (2013). Then we move on to discuss the international and domestic legal aspect of the concept of the aforementioned term, and then we turn to the types of disabilities. Then we come to the statement of procedures for diagnosing disability, first talking about the competent authority for diagnosis, and then the procedures to be followed for this purpose. Finally, we talk about the criterion by which the disabled are entitled to the rights stipulated in the relevant laws, as there are two criteria followed by the Iraqi legislator in this field: the first is medical and the second is economic. Note that we will only shed light on Iraqi legislation and the International Convention on the Rights of Persons with Disabilities because the research pages are limited to a certain number. We will address the draft first amendment to the Disability Care Law in some pages of the research to indicate the extent of the planned changes.